The Suitable Fabric for Thai Art Folding of Banana Leaves on Clothing - Chanakarn Ruangnarong (IJCAS (International Journal of Creative and Arts Studies), 2017)
Thailand has a uniquely long-standing tradition of arts and crafts. Thai art folding of banana leaves, probably the best-known such as food wrappers and precious handicrafts has been practiced to make colorful decorations for festivals. As time passed, roles of using parts of banana have been reduced but there has been an attempt to help conserve it only some art and craftsmanship. This research will study and analyze about Thai art folding of banana leaves, the folding technic from art and design, product and fashion for diversity of folding. Furthermore, Fabric is the key of this research to know the type of fabric suitable for folding. Thus, the experiment and practice show the fabric qualification by selected 9 properties included 1. Good stability 2. Good draping 3. Heat resistance 4. Smoothness 5. Balance 6. Wrinkle 7. Stretch 8. Strong 9. Soft with the wearable fabric are 1. Natural Fabric 1.1) Cotton 1.2) Linen 1.3) Muslin 1.4) Jute 1.5) Ramie 2.Man-made fabric 2.1) Polyester 2.2) Nylon 2.3) Organza 2.4) Satin 3. Blended Fabric 3.1) Cotton Spandex 3.2) Linen Viscose. The result is Polyester, Cotton Spandex and Linen Viscose respectively suitable for folding. In conclusion, the purpose of this research compiles the theory, technique, and method of Thai art folding of banana leaves. Moreover, the many types of folding technique from Thai art folding of banana leaves for clothing construction that can be a guideline and modified in the next stage for designers who interested in craftsmanship, culture, and tradition. Then, to create the guideline from the Thai art folding of banana leaves. Finally, the wearable art by using the clothing construction guideline from the Thai art folding of banana leaves.